P2TP2A Banda Aceh's Efforts in Developing Victims of Child Sexual Violence - Zahratun Aini; Kasmil S. Abdulwahid (Journal of Islamic Education and Ethics)
The child is the successor of the generation, the most important component of society for the family, religion, and nation. Sexual violence is a treatment that occurs through unwarranted coercion, causing psychological pressure or physical injury to the person who suffers it. If we want a better future for children, then every child needs good maintenance and education. Therefore, pusat pelayanan terpadu pemberdayaan perempuan dan anak (P2TP2A) is an institution that has authority over issues related to the deprivation of the rights of women and children. In 2020, Aceh was ranked ninth in the province of sexual violence against children in Indonesia, which in the previous year was ranked sixteenth. Related to regulation, Aceh has Qanun number 9 of 2019 on Child Protection in the implementation of violence handling and qanun Jinayah number 6 of 2014 as the basis for making decisions on cases of violence against children. The purpose of this study was to determine what efforts are made by P2TP2A in coaching victims of sexual violence against children. This study used a qualitative approach while applying observation, interviews, and literature review by collecting data from research, articles, news, or relevant sources. The subjects of this study were staff members of P2TP2A Banda Aceh. The results showed that the coaching efforts undertaken by P2TP2A Banda Aceh City are carried out through three stages, namely recording, identification of interventions, and service delivery. Services provided include health care, counseling, legal services, provision of safe housing, and social rehabilitation. The obstacles faced are budget problems and support from the community. The benefit of conducting this research is to see what efforts are being made by P2TP2A Banda Aceh towards sexual violence against women and children and what efforts are being made by the government, including P2TP2A Banda Aceh in the process of controlling the protection of women and children.